Determinants of Socially Oriented State Policy of Economic Relations Development - PETRUNENKO, Iaroslav V.; PODTSERKOVNYI, Oleg P.; KULINICH, Olha O. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
At the present stage of development of economic systems, a multitude of countries around the world are focused on implementing such a regulatory policy of the state that would enable sustainable development and formation of a socially oriented type of market economy, where the main goal is to ensure the welfare and high living standards of the population. Thus, the purpose of the research in this article is to identify the determinants of socially oriented state policy for the development of economic relations, respectively, the subject is to determine the strategic priorities of such policy. To achieve this purpose, the article employs general theoretical and special legal methods of research, in particular, the dialectical method of scientific cognition allowed to trace the current trends in the development of national policy, the comparative legal method allowed to perform a comparative analysis of strategic priorities of national policy in foreign countries, which reached a significant level of socio-economic development, analytical method applied in formulating generalized and elaborate conclusions based on the research findings. Based on the results of the study, the author came to the conclusion that the modern socially oriented state regulatory policy is based on the current form of state government, which determines the political regime of the country and the legislative basis for regulating the economic relations of economic entities, which operate in accordance with the formed institutional environment in the country.